Skin closure in arthroplasty surgery: Current practice. Issue 6 (6th July 2018) - Barrow, Jonathan; Divecha, Hiren; Board, Tim
Abstract : The study by Smith et al. (2010) concluded that clips are associated with 3 times the infection rate compared with subcuticular sutures in orthopaedic surgery ( P = .01).For hip surgery, there was a 4‐fold increase. We aimed to determine the trends and influences in skin closure and wound care for hip and knee arthroplasty in the northwest region as well as what would change surgeons' current practice. A short online survey was emailed to consultants in the northwest of England enquiring about their current practice in superficial skin closure, what has influenced this, and finally what would change their practice. Returned surveys were then analysed. A total of 45 consultants responded (response rate of 40.2%). In both hip and knee arthroplasty, clips were the most commonly used superficial skin closure material (53% and 63%, respectively). Personal experience was the greatest influence on the choice of closure material in both hip and knees (84% and 93% respectively). A total of 66% of hip and 76% of knee surgeons would change their closure material if there was evidence to support this. Hip and knee arthroplasty surgeons are influenced by their personal experience, and most use clips as their skin closure method. Most would change their practice with evidence of one material over another. We conclude that there is need for a prospective, well‐powered, multi‐centre randomised control trial to determine the skin closure material that has the lowest return‐to‐theatre rate in arthroplasty surgery.